2017
DOI: 10.1155/2017/7581531
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility Pattern ofE. coliO157:H7 Isolated from Traditionally Marketed Raw Cow Milk in and around Asosa Town, Western Ethiopia

Abstract: A cross-sectional study was conducted from October 2014 to July 2015 to determine the prevalence and populations of E. coli as well as the prevalence and antimicrobial susceptibility of E. coli O157:H7 isolated from raw milk. Biochemical and serological tests methods were used to confirm E. coli and E. coli O157:H7 and isolates were subjected to antimicrobial susceptibility test using the agar disc diffusion method. Out of 380 raw milk samples examined, 129 (33.9%) and 11 (2.9%) were contaminated with E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
72
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(99 citation statements)
references
References 17 publications
(22 reference statements)
12
72
12
Order By: Relevance
“…Similar with the present finding, showed that 23.7% samples from food of bovine origin harbored E. coli. Furthermore, 32% of raw milk samples were found to harbor E. coli, which is somewhat in agreement with the report of 33.9% by Disassa et al (2017). However, the prevalence is far lower when compared to the reports of Shunda et al (2013) from Mekelle town (44%) and far higher when compared to 26% prevalence reported by Farhan et al (2014) and 23.3% by Elbagory et al (2016).…”
Section: Discussionsupporting
confidence: 89%
“…Similar with the present finding, showed that 23.7% samples from food of bovine origin harbored E. coli. Furthermore, 32% of raw milk samples were found to harbor E. coli, which is somewhat in agreement with the report of 33.9% by Disassa et al (2017). However, the prevalence is far lower when compared to the reports of Shunda et al (2013) from Mekelle town (44%) and far higher when compared to 26% prevalence reported by Farhan et al (2014) and 23.3% by Elbagory et al (2016).…”
Section: Discussionsupporting
confidence: 89%
“…Escherichia coli O157 is considered as one of the most dangerous causes of gastrointestinal disorders, along with the cause of most cases of food poisoning around the world (13,14). Impact of E. coli O157 as a food-borne pathogen is increased in public places, such as dormitories and hostelry centers, especially hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, illegal slaughtering of animals in open fields, unhygienic slaughter practices in the abattoirs, and wide-spread tradition of consumption of raw meat (Kitfo dulet and Kurt) are potential risk factors in the country. Given that ruminants are natural reservoirs of Shiga toxin-producing Escherichia coli strains, higher prevalence is common in areas where fecal contamination is continuous, namely, farms, transportation trucks used to deliver animals to slaughtering houses, and slaughtering halls ( Bekele et al., 2014 ; Beyi et al., 2017 ; Disassa et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%